Wayang Kulit Ramayana Sebagai Ide Penerapan Motif Batik Pada Pembuatan Hand Bag - Ade Nur Hizliah; Wahyu Tri Atmojo; Raden Burhan Surya Nata Diningrat (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This design project is motivated by the declining interest of society, especially the younger generation, in the traditional art of Wayang Kulit Ramayana as part of Indonesia’s cultural heritage, which is being eroded by globalization. The lack of awareness regarding the importance of cultural preservation drives the need for innovative efforts that are relevant to today’s lifestyle. The aim of this project is to create batik motifs inspired by scenes from the Ramayana epic, to be applied to handbag products, thus reintroducing cultural values to society through functional and aesthetic media.The design process involves transforming visual representations of Ramayana scenes each containing deep moral messages and philosophies into batik motifs by combining stylization and the characteristic stylir technique of Wayang Kulit. The design method follows SP. Gustami’s theoretical approach, which includes three stages: exploration, design, and realization.This project has resulted in twelve batik motif designs, with twelve final works materialized as handbags made of mori cloth using the hand-drawn batik technique. It is hoped that this work can become a contemporary innovation in hand-drawn batik that not only enhances personal style but also serves as a means of preserving the cultural heritage of the Wayang Kulit Ramayana.